On the Reception of French Existentialism in the Cultural and Ideological Context of Late Stalinism (The Case of J.-P. Sartre) - Dmitry M. Tsyganov (Studia Litterarum)
The perception of J.-P. Sartre’s intellectual and creative activity in Soviet post-war criticism and literary criticism has repeatedly altered due to ideological and cultural factors. In the context of the global confrontation between two aesthetic systems, “modernism” and “socialist realism,” the existentialist Sartre was perceived as the leading representative of “decadent bourgeois culture.” However, the period between the second half of the 1940s and the first half of the 1950s was a watershed for Sartre’s emerging reputation in the USSR. From the ideological enemy, he began to be positioned as a “fellow traveler” of the Communist Party and, towards the end of the Stalinist era, as an “ally” of the Soviet regime. These changes influenced critical rhetoric and determined the angle of interpretation of the ideas of French existentialism. The scientific novelty of this article in the field of Russian and French studies is that it considers the “negative reception” of Sartre’s philosophy and work in connection with the opposition “bourgeois modernism” / “socialist realism.” A detailed analysis of texts appearing in central periodicals and archival sources enables us to reconstruct this implicit line of late Stalinist cultural policy.